Performance investigation of thermally enhanced polymer composite materials for microelectronics cooling. Issue 12 (December 2015) - Eveloy, Valérie; Rodgers, Peter; Diana, Antoine
Abstract: Driven by the low density, corrosion resistance, manufacturability, and low raw material and manufacturing costs of polymer composite materials, significant attention is being devoted to the innovation, characterization, and implementation of such materials. In this study the thermal and mechanical properties of a broad range of commercially available, injection moldable, thermally enhanced polymer composite materials are reviewed to help identify candidate materials that could replace conventional metal alloys in microelectronics cooling heat sink and heat exchanger applications. The material property characterization data reviewed consists of vendor data generated in accordance with applicable characterization standards. From twenty seven commercially-available polymeric composite materials, two promising groups of materials, namely polyphenylene sulfide (PPS) and polyimide 66 (PA66), are identified. A preliminary investigation of exchanger heat transfer rate is undertaken using computational fluid dynamics (CFD) to identify the envelope of thermally enhanced composite material thermal conductivities required for effective heat transfer in gas–liquid heat exchanger applications. The thermal performance of a thermally enhanced PPS, parallel plate cross-flow air–water heat exchanger prototype is shown numerically and experimentally to be comparable to that of a conventional aluminum exchanger having the same geometry, demonstrating the potential feasibility of replacing conventional metallic heat exchangers with thermally enhanced polymeric composite heat exchangers in microelectronic air–liquid cooling applications. Highlights: Review of thermal and mechanical properties of polymer composite materials. Promising materials identified for heat exchangers in microelectronics cooling. Numerical assessment of polymer composite heat exchanger thermal performance. Heat transfer feasibility of replacing metallic exchangers with polymer composites.